The Impact of Overall Intervention Model on Price of Wheat - Aljboori , Nihad S. Khalaf‏; Abdullah, Hiba H.; Noori, Nooruldeen A. (Iraqi Journal of Science, 2024)
The analysis of observed data at different time points is prominent to single problems when the scientist studied random sampling data over time restricts the applicability of many traditional statistical methods that require random sampling. The analysis of this data is usually mentioned to the stochastic process, in a special case, if it relates to time, then it is called time series [1]. The aim of our study is to focus on the case of observations that are made at certain times of the year, specifically in the autumn season, in equal periods of time, and we estimate the effect of interference on wheat prices n order to obtain the best predictive model and the best order of this model for the overall effect on the price of wheat for the coming years.